Existence of positive periodic solutions for two types of second-order nonlinear neutral differential equations with variable delay - Ardjouni,Abdelouaheb (Universidad Católica del Norte, Departamento de Matemáticas, 2013)
In this article we study the existence of positive periodic solutions for two types of second-order nonlinear neutral differential equation with variable delay. The main tool employed here is the Krasnosel-skii's fixedpoint theoremdealing withasum of twomappings, one is a contraction and the other is completely continuous. The results obtained here generalize the work of Cheung, Ren and Han [7.